Method of approximation of evolutionary inclusions and variational inequalities by stationary - Kasyanov, P.O.; Mel'nik, V.S.; Toscano, L. (Навчально-науковий комплекс "Інститут прикладного системного аналізу" НТУУ "КПІ" МОН та НАН України, 2005)
The method of finite-difference approximations, advanced by C. Bardos and H. Brezis for the nonlinear evolutionary equations, is generalized on differential-operational inclusions which are tightly connected to evolutionary variational inequalities in Banach spaces. Узагальнено метод кінцево-різницевих апроксимацій, розвинутий Бардосом і Брезисом для нелінійних еволюційних рівнять, на диференційно-операторні включення, які тісно пов’язані з еволюційними варіаційними нерівностями у банахових просторах. Обобщен метод конечно-разностных аппроксимаций, развитый Бардосом и Брезисом для нелинейных эволюционных уравнений, на дифференциально-операторные включения, которые тесно связаны с эволюционными вариационными неравенствами в банаховых пространствах.